El Vuelo de la Memoria - Castillo, Cármen (La Sociología en sus Escenarios, 2009)
Abstract. In Chile (1973), the political situation worsened more and more, the spacing of the MIR of the circle of Allende, the debates and the tensions in the left. With Salvador Allende we had a moral identification, almost familiar bows of friendship. We shared he himself combat against the right and the United States. Were, we miristas them, with him and elsewhere at the same time. Salvador Allende died to two of afternoon. They spent some hours of his solitary death in the Currency until the moment that arrived the news to us. The news of our solitude Resumen . In Chile (1973), la situación política se agravaba cada vez más, el distanciamiento del MIR del círculo de Allende, los debates y las tensiones en la izquierda. Con Salvador Allende teníamos una identificación moral, lazos de amistad casi familiares. Compartíamos el mismo combate contra la derecha y los Estados Unidos. Estábamos, nosotros los miristas, con él y en otra parte al mismo tiempo. Salvador Allende murió a las dos de la tarde. Pasaron algunas horas de su muerte solitaria en La Moneda hasta el momento que nos llegó la noticia. La noticia de nuestra soledad